DESAIN ALGORITMA DAN SIMULASI ROUTING UNTUK GATEWAY AD HOC WIRELESS NETWORKS - Meok, Nixson (Majalah Ilmiah Teknologi Elektro; Vol 8 No 2 (2009): (July - December) Majalah Ilmiah Teknologi Elektro, 2012)
Routing protocol to the wireless ad hoc networks is very needed in the communication process between some terminals, to send the data packet through one or several node(s) to the destination address where the network typology is always changing. Many previous works that discussed about routing ad hoc both for manet (mobile ad hoc networks) and wireless networks, but the emphasis have more focus on comparing the performance of several routing ad hoc. While in this work, there is a bulding of routing algorithm model to gateway in land to the nodes that analogized as a boat that move on the sea. With the assumption that the communication inter terminals to radio band of Very High Frequency, thus algorithm that built in the simulation based on the range gap of the HF frequency. The result of this simulation will be developed as the platform to implement the service development of multiuser communication